HUBUNGAN ANTARA PENGETAHUAN TENTANG SWAB NASOFARING TERHADAP PENGETAHUAN TENTANG KANKER NASOFARING PADA MAHASISWA DI MATARAM - Muhammad Sutan Maulana (Jurnal Medika Hutama, 2024)
Background: Nasopharyngeal carcinoma (KNF) is a malignant tumor that grows in the Rossenmuller Fossa area and at the top of the nasopharynx. KNF is a tumor that originates from epithelial cells that cover the surface of the nasopharynx. Worldwide, the incidence of nasopharyngeal carcinoma is rare, with less than 1 case per 100,000 population. However, in certain parts of the world, such as Indonesia, there are about 5-10 cases per 100,000 population. Therefore, this study aimed to correlate the knowledge of nasopharyngeal swab with the knowledge of nasopharyngeal cancer among university students in Mataram. Methods: This study is an analytic observational study with a cross sectional approach. The population in this study were students at the Faculty of Medicine, Mataram University. Results: In this study, the results for the greatest knowledge score were sufficient knowledge (score 12-15) of 107 people (53.5%), followed by poor knowledge (score <12) as many as 88 people (44%), and for good knowledge (score> 15) as many as 5 people (2.5%). The results of the spaerman test obtained a Sig. (2-tailed) of 0.003 (P < 0.005), and also obtained the correlation coefficient value for the variable knowledge of nasopharyngeal swabs is 0.206. Conclusion: There is a significant relationship between knowledge about nasopharyngeal swabs and knowledge about nasopharyngeal cancer in university students in Mataram.